An Assessment of Home-Based Care Programs in Uganda: Their Strengths and Weaknesses - Ebun, Walker Mary; Esther, Aceng; Denis, Tindyebwa; Juliet, Nabyonga; Peter, Ogwang; Paul, Kiiza (Ministry of Health Uganda, 2002)
Currently, lessons are being learnt from successful HIV/AID programs for policy decisions and program strengthening and implementation. This study assessed the Home-Based Care Programs in Uganda, highlighting their strengths and weaknesses, and relating these to their strategies. Using qualitative and quantitative methods, the following elements of care were assessed in seven Home-Based Care Programs: aims and objectives, provision and continuum of care, staffing, supplies and equipment, education, financing, costs of care, monitoring and evaluation, and impact. The findings were evaluated with the Best Practice criteria of relevance, sustainability, ethical soundness, effectiveness and efficiency. Comprehensiveness and delivery of AIDS care, integration with prevention and types of drugs were relevant to the family, community and national needs. Ethical principles of confidentiality and equity of access guided their approaches. Sustainability measures like networking, active community participation, including volunteer service were employed. Their periods of operation, 10-17 years, reflected medium term sustainability. Effectiveness was reflected in reported satisfaction with care and improvement in quality of life among high proportions of beneficiaries. Identified weaknesses include: weak management and financial controls; deficient records management; lack of defined outcome measures; heavy dependence on foreign funding; weak and informal health facilities linkage; a gap between the programs and the local political and administrative leaders; lack of national policy on AIDS home-based care. The facility outreach programs utilizing nursing personnel and large numbers of community volunteers for medical and enlarged psychosocial support appeared more efficient, from the large patient turnover and number of visits, low ratios of staff/patients and staff/visits conducted and lower average costs of care. There is a need for a national policy on home-based care, for standards and guidelines and internal funding. The home-based care programs require strengthening for enhanced efficiency and effectiveness with regards to management, and resource utilization.
Keywords: Home-Based Care Programs; Home -Based care; Best Practice criteria; Community-volunteers